Rehabilitasi Tanah Aluvial Terdegradasi dengan Pupuk Kandang Kambing dan POC Tahu untuk Meningkatkan Produktivitas Okra - Astar, Ismail; Setiawan; Rahayu, Sri; Suyanto, Agus (Rawa Sains: Jurnal Sains STIPER Amuntai, 2025)
Marginal alluvial soils are characterized by low fertility, acidic pH, and limited nutrient availability, which constrain agricultural productivity. This study investigated the effects of goat manure and liquid organic fertilizer (POC) from tofu wastewater on okra growth and yield in alluvial soil. A completely randomized factorial design was employed with two factors: goat manure doses (50, 100, 150 g/polybag) and tofu wastewater POC concentrations (10%, 20%, 30%), each replicated three times, resulting in 27 experimental units. Soil analysis revealed significant improvements in chemical and physical properties after treatment application. Initial soil pH increased from 4.82 to 5.9, organic carbon content rose from 1.82% to 3.05%, total nitrogen increased from 0.16% to 0.42%, and available phosphorus improved from 18.3 ppm to 92.14 ppm. Physical properties also enhanced with bulk density decreasing from 1.62 to 1.24 g/cm³ and total porosity increasing from 34.21% to 46.37%. ANOVA analysis showed significant effects of POC concentration on plant height and fruit weight, with 20% concentration producing optimal results. Goat manure significantly influenced fruit weight, with the highest dose (150 g/polybag) yielding 89.44 g compared to 56.96 g at the lowest dose. No significant interactions were observed between the two factors. The results demonstrate that combined application of goat manure and tofu wastewater POC effectively transforms degraded alluvial soil into fertile growing medium, supporting sustainable okra production in marginal lands.